Implementasi Peraturan Daerah Kabupaten Tapanuli Selatan Nomor 10 Tahun 2006 Tentang Retribusi Tempat Rekreasi Dan Olahraga - Dermina Dalimunthe, Adhia Rahma Shinta Harahap & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The problem in this study is how far the implementation of Article 7 Paragraph (2) of the Regional Regulation of South Tapanuli Regency Number 10 of 2006 concerning Retribution for Recreation and Sports Places in Aek Sijorni, Aek Libung Village, Sayur Matinggi District, South Tapanuli Regency. Because the levies collected are not in accordance with existing regulations. The purpose of this study is to describe and analyze the implementation of Article 7 Paragraph (2) of the Regional Regulation of South Tapanuli Regency Number 10 of 2006 concerning Retribution for Recreational and Sports Places in Aek Sijorni, Aek Libung Village, Sayur Matinggi District, South Tapanuli Regency. The author raises the formulation of the problem, namely how the implementation of the levy policy for recreation areas in Aek Sijorni and what are the inhibiting factors for the implementation of the levy policy for recreational areas in Aek Sijorni, South Tapanuli Regency. The research method used in this research is a qualitative approach using descriptive methods, namely describing the phenomena or vices that occur in the field. Data collection instruments used in this study consisted of interviews, observation, and documentation. The result of this research is that the implementation of Article 7 Paragraph (2) of the Regional Regulation of South Tapanuli Regency Number 10 of 2006 concerning Retribution for Recreational and Sports Places that from the government of South Tapanuli Regency has not been implemented because of the many regulations governing the amount of fees for different recreational areas. However, in its implementation, the South Tapanuli Regency government has carried out socialization and mediation with the community together with the Head of Sayur Matinggi District and the South Tapanuli Regency Tourism Office. The inhibiting factor in the Implementation of Article 7 Paragraph (2) Regional Regulation of South Tapanuli Regency Number 10 of 2006 concerning Retribution for Recreational and Sports Places in Aek Sijorni is the status of land ownership towards Aek Sijorni, the Mindset of the People who are Still Underdeveloped, Lack of Communication between the Community and the Government and Local Community Employment Status.